2019
DOI: 10.1016/j.jcpx.2019.100013
|View full text |Cite
|
Sign up to set email alerts
|

Tensor calculus in spherical coordinates using Jacobi polynomials. Part-I: Mathematical analysis and derivations

Abstract: This paper presents a method for the accurate and efficient computations on scalar, vector and tensor fields in three-dimensional spherical polar coordinates. The methods uses spinweighted spherical harmonics in the angular directions and rescaled Jacobi polynomials in the radial direction. For the 2-sphere, spin-weighted harmonics allow for automating calculations in a fashion as similar to Fourier series as possible. Derivative operators act as wavenumber multiplication on a set of spectral coefficients. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…We use 256 × 128 Fourier modes in the x, y directions, and 32 Chebyshev modes in the z direction, all using 3/2 dealiasing. The Chebyshev tau method balances energy to exponentially high accuracy; exact energy conservation could be still be imposed, however, by formulating a self-adjoint system with an alternative orthogonal polynomial basis [50,98,99].…”
Section: E Quasigeostrophic Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…We use 256 × 128 Fourier modes in the x, y directions, and 32 Chebyshev modes in the z direction, all using 3/2 dealiasing. The Chebyshev tau method balances energy to exponentially high accuracy; exact energy conservation could be still be imposed, however, by formulating a self-adjoint system with an alternative orthogonal polynomial basis [50,98,99].…”
Section: E Quasigeostrophic Flowmentioning
confidence: 99%
“…The flow vanishes at the outer wall; u(t, R out , θ) = 0. The tangential velocity at the inner wall is a time-dependent regularized square wave u θ (t, R in , θ) = arctan(50 sin(t/n rot )) arctan (50) .…”
Section: F Stokes Flowmentioning
confidence: 99%
“…The dynamics at the poles are similar to those on a non-rotating flat plane and the non-inertial effects matter the most at the equator. method with a basis of spin-weighted spherical harmonics Vasil et al 2019); more details on the method can be found in the appendix of Mickelin et al (2018). A spectral expansion with a cut-off max = 256 was found to be sufficient to obtain converged solutions.…”
Section: β−Plane Solutionsmentioning
confidence: 99%
“…This complex basis has the nice property that rotations by π/2 around the vertical axis are obtained by multiplying A 1 and A 2 by the imaginary unit i, which is conveniently summarized with the components while the basis is unaffected; see e.g. Vasil et al [22].…”
Section: Composed Symmetry Classes; Backward Transformation To Real Axesmentioning
confidence: 99%
“…For the threefold, fourfold and sixfold axes, the following component vanishes C 11 12 = 1 4 (c 11 11 − c 22 22 − c 12 12 + c 11 22 + ic 11 21 + ic 22 12 + c 21 22 − c 22 11 − ic 11 12 − ic 22…”
mentioning
confidence: 99%